THE EFFECT OF CORPORATE REPUTATION TOWARD BRAND LOYALTY OF GOJEK MANADO - Lenak, Sendy A.; Lapian, S.L.H.V. Joyce; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2019)
Abstract: Usually consumer must use transportation like bus, mikrolet, taxi and motor taxi,, but now consumer have freedom to choose a transportation model with more convenience, cheaper, faster, more reliable, and very accessible only with smartphone application.. The online transportation businesses in Manado City that are operating right now are Gojek, Grab, and Uber. As the traffic jam at this city is increasing day by day, itâ€™s helps people so much. It also has an affordable price. This study is to investigate the influence of corporate reputation on the brand loyalty of Gojek. This research use a quantitative method and simple regression analysis with total sample 50 university student. The result shows that the corporate reputation has a significantly influence the brand loyalty at Gojek Manado. The customer choose Gojek as their priority in choosing an online transportation because of several causes which are: Gojek always give the customer a good service and always take a good responsibility to the customers. The management of Gojek Manado should stabilize the system in the working place to create a greater corporate reputation in purpose to get the consumer loyalty and lead the online transportation business.Â Keywords: brand loyalty, corporate reputation